Finite element models of intervertebral disc: recent advances and prospects - Tianze Sun; Junlin Wang; Xin Liu; Huagui Huang; Jinzuo Wang; Moran Suo; Jing Zhang; Zhonghai Li (Annals of Medicine)
Objectives The incidence rate of intervertebral disc degeneration (IVDD) is increasing year by year, which brings great harm to our health. The change of biomechanical factors is an important reason for IVDD. Therefore, more and more studies use finite element (FE) models to analyze the biomechanics of spine.Methods In this review, literatures which reported the FE model of intervertebral disc (IVD) were reviewed. We summarized the types and constructional methods of the FE models and analyzed the applications of some representative FE models.Results The most widely used model was the nonlinear model which considers the behavior of porous elastic materials. As more advanced methods, More and more models which involve penetration parameters were used to simulate the biological behavior and biomechanical properties of IVD.Conclusions Personalized modeling should be carried out in order to better provide accurate basis for the diagnosis and treatment of the disease. In addition, microstructure, cell behavior and complex load should be considered in the process of model construction to build a more realistic model.